Boundary between N1 and N2 Lymph Node Descriptors in the Subcarinal Zone in Lower Lobe Lung Cancer: A Brief Report. Issue 7 (July 2016) - Isaka, Mitsuhiro; Kondo, Haruhiko; Maniwa, Tomohiro; Takahashi, Shoji; Ohde, Yasuhisa
ABSTRACT : Introduction: : In the International Association for the Study of Lung Cancer (IASLC) lymph node (LN) map, some LNs in the subcarinal space defined as #10 (N1) in the Naruke map were changed to #7 (N2). We aimed to validate the boundary between N1 and N2 in the subcarinal zone. Methods: : We reviewed the records of 399 consecutive patients who had undergone complete resection for lower lobe non–small cell lung cancer. Involved lymph node stations were classified as N1 by both maps (N1 group), N1 by the Naruke map but reclassified as N2 by the IASLC map (#10 [subcarinal] group), and N2 by both maps (N2 group). The survival rates among these groups were compared using Kaplan‐Meier and log‐rank analyses. Results: : LNs were classified as N0, N1, and N2 in 268, 67, and 64 patients, respectively, on the IASLC map and as N1 and N2 in 82 and 49 patients, respectively, on the Naruke map. The 5‐year disease‐free survival rates were 81.7% for N0, 50.9% for N1, 33.3% for the #10 (subcarinal) group, and 24.4% for N2. The rates of the N1 and #10 (subcarinal) groups were significantly different ( p = 0.027), but those of the N2 and #10 (subcarinal) groups were not ( p = 0.78). On multivariate analysis, metastatic disease in the LNs of #10 in the subcarinal space was an independent prognostic factor for patients classified as N1 on the Naruke map (hazard ratio = 2.47, 95% confidence interval: 1.17–4.85, p = 0.019). Conclusion: : All lymph nodes in the subcarinal space should be defined as #7 (N2) for prognosis.